High-performance broadband photodetectors based on all-inorganic perovskite CsPb(Br/I)3 nanocrystal/CdS-microwire heterostructures. Issue 19 (22nd March 2021) - Li, Haixia; Lin, Weiwei; Ma, Liang; Liu, Yang; Wang, Yu; Li, Ao; Jin, Xiaorui; Xiong, Lun
Abstract : The high performance photodetector based on CsPb(Br/I)3 -NC/CdS-MW heterostructures showed broadband photodetection that covers UV-VIS-NIR range due to the charge transfer at the heterojunction interface and the absorption capability of CsPb(Br/I)3 . Abstract : High-performance broadband photodetectors that can operate at UV, visible, and near-infrared wavelengths have been fabricated based on CsPb(Br/I)3 nanocrystal (NC)/CdS-microwire (MW) heterostructures. Under an incident light illumination of 365, 530, and 660 nm, the CsPb(Br/I)3 -NC/CdS-MW-heterostructure-based photodetector exhibited a superior photosensitivity and broader spectral response than those of a bare-CdS-MW-based photodetector, which can be attributed to the light-trapping ability of the CsPb(Br/I)3 NCs and charge-transfer efficiency at the CsPb(Br/I)3 -NC/CdS-MW-heterojunction interface. The photodetector based on the CsPb(Br/I)3 NC/CdS-MW heterostructure also exhibited a good response to near-infrared light (760 and 810 nm) because the produced heterojunction facilitates the spatial separation of the photogenerated carriers, and the carriers are transferred from the CsPb(Br/I)3 NC part to the CdS MW part through diffusion due to the relatively long diffusion length in the CsPb(Br/I)3 layer. Therefore, the proposed photodetectors are promising for constructing high-performance broadband optoelectronic devices.